The Role of Blood Pressure in Carotid Plaque Incidence: Interactions With Body Mass Index, Age, and Sex-Based on a 7-Years Cohort Study - Liu, Jian; Ma, Xuehua; Ren, Xue-Ling; Xiao, Hong; Yan, Leyuan; Li, Zhuorong; Wang, Shengshu (Frontiers in Physiology, 2021)
Abstract Background: Although high blood pressure (BP) is a risk factor for carotid plaque, its long-term prognostic value might be underestimated due to its confounding interactions with other cardiovascular risk factors (CRFs). Therefore, we conducted a 7-years’ prospective cohort study to evaluate the prognostic value of BP for the incidence of carotid plaque. Methods: The subjects enrolled in 2011 were without carotid plaque at baseline and were followed up for incident carotid plaque in 2018. Multivariate Cox proportional-hazards models were used to evaluate the association between blood pressure and carotid plaque incidence. Results: During the follow-up study, the incidence of carotid plaque was 36.5%. The significant positive linear trend showed that subjects with higher BP levels at the baseline were more likely to develop carotid plaques at the end. Especially in the female subpopulation, after adjusting for other CRFs, carotid plaque was associated with higher BP (adjusted HR 1.52, 95% CI 1.02 - 2.26), pulse pressure (PP) (adjusted HR 1.15, 95%CI 0.76 - 1.75), and mean arterial pressure (MAP) (adjusted HR 1.44, 95%CI 1.00 - 2.08). When adjusted with CRFs, and the potential antagonistic interactions between BP categorical indicators and CRFs, carotid plaque was associated with significantly increased HRs for high BP, PP and MAP (HR 27.71, 95% CI 2.27-338.64; HR 14.47, 95% CI 1.53-137.18; HR 9.97, 95% CI 1.29 - 77.28). Conclusion: High BP indicators might be associated with higher HRs of carotid plaque after adjusting for interactions between BP indicators and BMI, age and gender. This suggests that, with the increase of age, the incidence of carotid plaque in female adults with high BP indicators might increase significantly.